Pemberdayaan Ekonomi Kreatif Melalui Pendampingan Praktisi Usaha Dalam Penguatan Jiwa Kewirausahaan Siswa SMK - Puput Erna Sari; Jesika Melina Simamora (Yayasan Cerdas Pedia Indonesia, 2025)
This community service initiative aims to enhance the entrepreneurial spirit of students at SMKN 1 Jorlang Hataran through mentoring by creative business practitioners. Utilizing Participatory Action Research (PAR) and experiential learning theory, the program engaged twenty students in